Student usage of Lund University Pole-Zero Explorer interactive tool in automatic control teaching - Heskebeck, Frida ; 0000-0002-6831-5119; Tufvesson, Pex ; 0009-0005-8459-1147; Hällström, Ask (European Journal of Control, 2025)
This study examines the effectiveness of LU-PZE, a web-based interactive tool designed to help students visualize and interact with fundamental concepts in automatic control. A total of 200 students enrolled in an introductory course on automatic control had the option to use LU-PZE as an additional resource for learning. LU-PZE offers users randomized quizzes, structured assignments, and real-time visualizations of theoretical concepts. An analysis of student usage shows that LU-PZE successfully increased student engagement and improved their understanding of automatic control principles. Student feedback also reveals that the students appreciate interactive tools for learning. These findings suggest that LU-PZE can be a valuable tool for teachers to promote active learning and enhance student outcomes in introductory courses in automatic control.
Publisher Copyright: © 2025 The Authors
Keywords: Computer aided learning; Control courses and labs; Control education; Gamification; Interactive tools; Teaching